POTENSI PEMANFAATAN DAGING BUAH SEMU JAMBU METE (Anacardium occidentale) SEBAGAI ABON - Slamet Mardiyanto Rahayu; Luis Da Costa (Nusantara Hasana Journal, 2025)
Anacardium occidentale grows abundantly on Lombok Island and is locally known as jambuk nyebet or cashew nut. Currently, the use of Anacardium occidentale is limited to its cashew fruit. Therefore, other parts, such as the flesh of the pseudo-fruit of Anacardium occidentale, are not utilized and are simply thrown away as waste. However, the flesh of the pseudo-fruit can be processed into shredded meat. Based on this description, this study is necessary to determine the potential use of the pseudo-fruit flesh of cashew (Anacardium occidentale) as shredded meat. Shredded meat of cashew is a type of preserved food made from the flesh of the pseudo-fruit of cashew which is processed in such a way that it resembles fibers, then added with spices and fried. Shredded meat is a snack or ready-to-eat side dish. Shredded floss has dry, crunchy, and savory characteristics.